Context and Implications Document for: The contribution of intersectionality to quantitative research into educational inequalities. Issue 2 (25th June 2018) - Codiroli McMaster, Natasha; Cook, Rose
Abstract : This guide accompanies the following article: Codiroli McMaster, N. & Cook, R. (2018) The contribution of intersectionality to quantitative research into educational inequality, Review of Education, https://doi.org/10.1002/rev3.3116 .